2021
DOI: 10.3389/fimmu.2021.614347
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Targeting of Neutrophil Extracellular Traps Improves Primary and Secondary Intention Wound Healing in Mice

Abstract: BackgroundNeutrophils are the first responders in wound healing after injury that mediate pro- and anti-inflammatory activities i.a. through the formation of extracellular traps (NETs). However, excessive NETs presence in wound tissue can cause local hyperinflammation and -coagulation resulting in delayed wound healing. To improve wound healing, we aimed to examine the role of NETs and DNase1 on primary and secondary wound healing.MethodsThe study included 93 C57BL/6 mice, with 3 different genotypes: wildtype,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 64 publications
0
46
0
1
Order By: Relevance
“…Targeting neutrophil function in post burn injury might serve as an alternative treatment option in severe cases with exacerbated neutrophil activation. Beneficial effects of anti-NETs therapy have already been demonstrated in various neutrophil-mediated inflammatory diseases and conditions, including wound healing 60 , inflammatory arthritis, pulmonary fibrosis, inflammatory bowel disease, and sepsis 61 . Determining the full therapeutic potential of NETosis inhibition following burn trauma will merit future investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Targeting neutrophil function in post burn injury might serve as an alternative treatment option in severe cases with exacerbated neutrophil activation. Beneficial effects of anti-NETs therapy have already been demonstrated in various neutrophil-mediated inflammatory diseases and conditions, including wound healing 60 , inflammatory arthritis, pulmonary fibrosis, inflammatory bowel disease, and sepsis 61 . Determining the full therapeutic potential of NETosis inhibition following burn trauma will merit future investigations.…”
Section: Discussionmentioning
confidence: 99%
“…The most common treatment is DNase I, which dismantles the scaffold of NET structures, and recombinant human DNase I is cost-effective with no known adverse effects. Upon systemic DNase I administration, diabetic mice show reduced wound areas, enhanced re-epithelialization, and accelerated wound healing [ 7 , 84 , 96 ]. However, DNase I has little effect on histones, elastase, or other components bound to NETs, which may be released into the bloodstream by the simple destruction of the NET scaffold, resulting in proteolytic tissue injuries [ 29 ].…”
Section: Anti-net Treatments In Wound Healingmentioning
confidence: 99%
“… H3cit and wound aera decreased [ 12 ] Tripeptide (Thr-Asp-F-amidine) Topically Wound closure and re-epithelialization accelerated [ 98 ] DNase 1 Pulmozyme 10 mg/kg i.p. Superior scar scores and wound closure time [ 96 ] Dornase alfa 10 μg i.v. 50 μg i.p.…”
Section: Anti-net Treatments In Wound Healingmentioning
confidence: 99%
“…Neutrophils not only inhibit healing by releasing soluble mediators and excessive ROS but they also secrete particles with pro-inflammatory microRNAs (miR-23a and miR-155) that can cause tissue damage (12). Wong et al showed the deletion of key NETosis enzymes, or the inhibition of the "Nod-like receptor protein (NLRP3) inflammasome-NETs" inflammatory loop, can improve angiogenesis and accelerate wound healing (13). The neutropenia model can accelerate the speed of wound epithelial closure without changing the overall quality of the wound healing process.…”
Section: Neutrophilsmentioning
confidence: 99%